A soluble form of the Mer receptor tyrosine kinase inhibits macrophage clearance of apoptotic cells and platelet aggregation - Sather, Susan (American Society of Hematology, 2007)
Membrane-bound receptors generate soluble ligand-binding domains either by proteolytic cleavage of the extracellular domain or alternative mRNA splicing yielding a secreted protein. Mertk (Mer) is in a receptor tyrosine kinase family with Axl and Tyro-3, and all 3 receptors share the Gas6 ligand. Mer regulates macrophage activation, promotes apoptotic cell engulfment, and supports platelet aggregation and clot stability in vivo. We have found that the membrane-bound Mer protein is cleaved in the extracellular domain via a metalloproteinase. The cleavage results in the production of a soluble Mer protein released in a constitutive manner from cultured cells. Significant amounts of the soluble Mer protein were also detected in human plasma, suggesting its physiologic relevance. Cleavage of Mer was enhanced by treatment with LPS and PMA and was specifically inhibited by a tumor necrosis factor α-converting enzyme metalloproteinase inhibitor. As a decoy receptor for Gas6, soluble Mer prevented Gas6-mediated stimulation of membrane-bound Mer. The inhibition of Gas6 activity by soluble Mer led to defective macrophage-mediated engulfment of apoptotic cells. Furthermore, soluble Mer decreased platelet aggregation in vitro and prevented fatal collagen/epinephrine-induced thromboembolism in mice, suggesting a potential therapeutic use for soluble Mer in the treatment of clotting disorders.